Penyembunyian Pesan Terenkripsi pada Citra menggunakan Algoritma LSB dan Transposisi Kolom - Kiswara Agung Santoso; Ahmad Tanto Wiraga; Abduh Riski (Journal of Applied Informatics and Computing, 2022)
Data security is a very important thing to do so that messages or information are sent to someone who is not known by unauthorized persons. Data security techniques that The ones that are often used today are cryptography and steganography. In this study, the data is to be secured in text. To increase security, text messages are first encrypted using the vigenere algorithm and column transposition. This text message is then hidden into an image (cover image). The encrypted text message was hidden in the image using the LSB algorithm and column transposition. The results of the study show that the virtual stego image generated is very effective similar to the original image. Based on the results of the MSE and PSNR analysis, it can be seen that the resulting image quality can be categorized as good. This can be seen from the PSNR value above 50 dB and some even above 60 dB. Based on the results of the LSB analysis, the stego image does not look strange so it will not be suspected by unauthorized people that there is a hidden message in the image.